MS-Stability Analysis of Predictor-Corrector Schemes for Stochastic Differential Equations - Zeghdane, R.; Tocino, A. (Discontinuity, Nonlinearity, and Complexity, 2026)
Deterministic predictor-corrector schemes are used mainly because of their numerical stability which they inherit from implicit counterparts of their corrector schemes. In principle these advantages carry over to the stochastic case. In this paper a complete study for the linear MS-stability of the oneparameter family of weak order 1.0 predictor-corrector Taylor schemes for scalar stochastic differential equations is given. Figures of the MS-stability regions that confirm the theoretical results are shown. It is also shown that mean- square A-stability is recovered if the parameter is increased.